Evaluasi Kepuasan Mahasiswa terhadap Sistem Informasi Penjadwalan Kuliah Biro Administrasi Umum dan Keuangan Universitas Xyz - Tangkas Udiono (Bina Nusantara University, 2013)
One way to identify the success indicator of the use of information systems is conducting a survey of user satisfaction. Measuring the quality of Information Systems of Registration and Lecture Scheduling at the Bureau of Administration and Finance University of XYZ is important because it aims to find out how far the role and utilization of existing information systems run. This research aims to investigate the faktors that influence user satisfaction of the information system. Data are collected through the distribution of questionnaires with the number of respondents as much as 378 students. The data collected are analyzed using sampling techniques. The results of the regression analysis and the correlation between Information System Quality and Information Quality affect student satisfaction by 6.6% and 4.9%.